Pop fiction : the song in cinema - Lannin, Steve; Caley, Matthew (Intellect Books, 2005)
Pop Fiction's unique essays individually consider one song within a cinematic context. Unlike previous collected volumes about pop music in film, where a generalised approach has been adopted, this offers instead a close examination of two pervasive and significant mediums in combination. The collection introspects, assembling the pop song into various guises and documenting how individuals dissemble the multiple roles that the pop song plays in cinematic moments. The song as: role-play, memory trigger, narrator, ghost, marketing device, translator, alienator, membership rite etc. All provide.